2013
DOI: 10.1109/tifs.2012.2225048
|View full text |Cite
|
Sign up to set email alerts
|

Touchalytics: On the Applicability of Touchscreen Input as a Behavioral Biometric for Continuous Authentication

Abstract: We investigate whether a classifier can continuously authenticate users based on the way they interact with the touchscreen of a smart phone. We propose a set of 30 behavioral touch features that can be extracted from raw touchscreen logs and demonstrate that different users populate distinct subspaces of this feature space. In a systematic experiment designed to test how this behavioral pattern exhibits consistency over time, we collected touch data from users interacting with a smart phone using basic naviga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
590
3
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 713 publications
(605 citation statements)
references
References 25 publications
3
590
3
9
Order By: Relevance
“…Han et al [22] suggested using accelerometer data to infer the GPS coordinates of a mobile device within a 200m radius from the real location. Frank et al [19] presented a continuous authentication system based on 30 touchbased gestures. Their SVM and kNN detection algorithms resulted in 0%-4% EER depending on whether training and testing were performed during the same user session.…”
Section: Gesture-based Authenticationmentioning
confidence: 99%
“…Han et al [22] suggested using accelerometer data to infer the GPS coordinates of a mobile device within a 200m radius from the real location. Frank et al [19] presented a continuous authentication system based on 30 touchbased gestures. Their SVM and kNN detection algorithms resulted in 0%-4% EER depending on whether training and testing were performed during the same user session.…”
Section: Gesture-based Authenticationmentioning
confidence: 99%
“…Traditionally, these included keyboards, [11], [15], [19], and mouse [2], [18], [38]. Now, modern smartphones also provide an array of sensor information, which can be used similarly to construct user profiles based on touchscreen swipes [4], [14], gait analysis [12], [27], and other metrics. These signals are collected from the legitimate user and then analyzed at authentication time to verify the identity of the user attempting to log in.…”
Section: A Behavioral Biometricsmentioning
confidence: 99%
“…The TouchAnalytics [15] dataset is a behavioural trait collected through strokes in mobile touchscreen interaction. TouchAnalytics is composed of 30 attributes derived from observed strokes performed by 41 users.…”
Section: Datasetmentioning
confidence: 99%
“…The number of stroke attempts is different for each user. Thus, a stroke is defined in [15] as a trajectory encoded as a sequence of vectors with real numbers, s n = (x n , y n , t n , p n , A n , o f n , o ph n ) where n ∈ 1, 2, ..., N enumerates the number of strokes (and there are N strokes), with location x n , y n , time stamp t n , pressure on screen p n , area A n occluded by the finger, finger orientation o f n , and phone orientation o ph n which can be landscape or portrait. Therefore, it is possible to derive the information about area covered, stroke pressure, direction, velocity and acceleration from the above raw data.…”
Section: Datasetmentioning
confidence: 99%